Survey of aqueous solubility, appearance, and pH of plant protein powders from carbohydrate and vegetable oil production. (November 2020) - Ebert, Sandra; Gibis, Monika; Terjung, Nino; Weiss, Jochen
Abstract: There is a need to have functional protein-rich ingredients to formulate a range of vegan and vegetarian products. However, available proteins vary in functionality and in particular in solubility, even if derived from the same plant source. In this survey, appearance, native pH, and aqueous solubility of 26 plant proteins were assessed. Solubility correlated with purity and extraction process applied and differences in between plant sources were related to protein types present in the raw material. For example, proteins with a prevalence of prolamins (wheat) or glutelins (rice) had lower solubilities than those from pea and sunflower, which consist almost exclusively of globulins and albumins. Moreover, solubility of pea protein isolates was between as little as 8% to as much as 50%, while less pure sunflower meals varied only between 19% and 22%. Extraction procedures further affected appearance e.g. due to pigment degradation and/or non-enzymatic browning. This study serves as reference to researchers currently working with various protein powders and highlights the need to establish relationships between base raw material properties such as solubility, pH, appearance, and applicability in the design of food matrices. Highlights: Biological origin and extraction approach cause variations in crude protein solubility. Crude protein solubility correlates with the amount of albumins. The choice of extraction techniques impacts powder appearance and native pH.